A transcriptomics study of hereditary angioedema attacks. - Castellano, Giuseppe; Divella, Chiara; Sallustio, Fabio; Montinaro, Vincenzo; Curci, Claudia; Zanichelli, Andrea; Bonanni, Erika; Suffritti, Chiara; Caccia, Sonia; Bossi, Fleur; Gallone, Anna; Schena, Francesco Paolo; et al. (J Allergy Clin Immunol, 2018)
BACKGROUND: Hereditary angioedema (HAE) caused by C1-inhibitor deficiency is a lifelong illness characterized by recurrent acute attacks of localized skin or mucosal edema. Activation of the kallikrein/bradykinin pathway at the endothelial cell level has a relevant pathogenetic role in acute HAE attacks. Moreover, other pathways are involved given the variable clinical expression of the disease in different patients. OBJECTIVE: We sought to explore the involvement of other putative genes in edema formation. METHODS: We performed a PBMC microarray gene expression analysis on RNA isolated from patients with HAE during an acute attack and compared them with the transcriptomic profile of the same patients in the remission phase. RESULTS: Gene expression analysis identified 23 genes significantly modulated during acute attacks that are involved primarily in the natural killer cell signaling and leukocyte extravasation signaling pathways. Gene set enrichment analysis showed a significant activation of relevant biological processes, such as response to external stimuli and protein processing (q < 0.05), suggesting involvement of PBMCs during acute HAE attacks. Upregulation of 2 genes, those encoding adrenomedullin and cellular receptor for urokinase plasminogen activator (uPAR), which occurs during an acute attack, was confirmed in PBMCs of 20 additional patients with HAE by using real-time PCR. Finally, in vitro studies demonstrated the involvement of uPAR in the generation of bradykinin and endothelial leakage. CONCLUSIONS: Our study demonstrates the increase in levels of adrenomedullin and uPAR in PBMCs during an acute HAE attack. Activation of these genes usually involved in regulation of vascular tone and in inflammatory response might have a pathogenic role by amplifying bradykinin production and edema formation in patients with HAE.